THE TALIBAN'S SURVIVAL: FROM POST-2001 INSURGENCY TO 2020 PEACE DEAL WITH THE UNITED STATES - Taufiq -E- Faruque (Universitas Muhammadiyah Malang, 2019)
The 2020 United States (US)-Taliban peace deal has essentially made the Taliban movement as one of the most durable and resilient insurgent groups in today's world. Following the 'levels of analysis' of international relations as an analytical framework, this paper explores the reasons behind the survival of the Taliban insurgency in an integrative framework that organizes the individual and group, state, and international level dynamics of this insurgency in a single account. The paper argues that the defection of politically and economically marginalized individual Afghans, the multilayered and horizontal structure of the Taliban insurgency, regional power configuration in South Asia, and the lack of a coherent post-invasion strategy of the US and its allies factored into the survival of the Taliban insurgency that resulted in a peace deal between the Taliban and the US.